Phatic and Politeness on Women’s Communication in Facebook: Humanistic Teaching Perspective of Being Polite in Social Media - Rosita Ambarwati; Joko Nurkamto; Riyadi Santosa (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
Technological developments have a wide impact on many things, one of which is the development of communication through social networking. The interesting thing about the Facebook phenomenon is that most of the users are women. Women who are identical with polite behavior are very interesting to study. This study aims to (1) Identify the form of women’s phatic speech acts on Facebook. (2) Describe the politeness strategy of women’s communication on Facebook, (3) to dig deeper into the extent of women politeness in Facebook through the humanistic teaching perspective. This research is descriptive qualitative research using pragmatic approach. The subjects of the study were women aged 25-50 years. Data is female speech on Facebook social networking. Data selection is done with certain consideration using purposive sampling. Data were collected using a method of referring and noting to a number of speeches containing a form of phatic expression. Test the validity of data is done through credibility test that is by extension of observation and member check. Data analysis was done based on Spradley's analysis model which was divided into 4 stages, namely domain analysis, taxonomic analysis, contextual analysis and cultural theme analysis. The results achieved are: (1) The form of phatic expressions seen from the analysis of speech acts in which the act of speech phatic ranked highest. (2) The characteristics of visible women language are, using polite expression, using indirect sentences, using adjectives, using question tags and humor. (3) The dominant function of the phatic is to maintain friendship and harmony of relationships. (4) Internet-based communication media provide flexibility for women to interact and establish relationships. (5) phatic communication on Facebook becomes dominant because the form of communication is not face to face directly so that the expression of the speaker cannot be seen and the comments that appear cannot be determined time so that the honesty of the less acceptable speech. This has a tendency as a form of introducing space. The women communication in Facebook through the phatic speech acts can be a source of learning approach to be polite in uttering utterances.